Pelatihan Pembuatan Minuman Herbal Imunomodulator untuk Pencegahan COVID-19 pada Forum SA3 Bidakara, Jakarta Selatan - Yuniar Zen; Abdul Gani Soulisa; Bernard Iskandar; Wiena Widyastuti (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2022)
During the COVID-19 pandemic, it is essential to maintain a healthy condition to reduce the risk of exposure to COVID-19. One way is to take vitamins or herbal-based supplements. Samilakor, the abbreviation of 'Sari Minuman Rempah asli Lawan Korona,' can modulate and increase immunity. The training target for making Samilakor is the SA3 Bidakara Forum, South Jakarta, an online community initially formed as an Islamic forum at the Al Hidayah Mosque, South Jakarta. This training includes knowledge about COVID-19, immunomodulators, how to process spices, and making Samilakor herbal drink. The training on making herbal drinks is conducted through an online seminar (webinar) via the Zoom platform. Participants' knowledge was assessed by pre-test and post-test, conducted online via Google Form. The success indicator of the training can be seen from the increased knowledge of participants in knowledge about COVID-19 and the process of making herbal drinks. The statistical analysis used is paired t-test. The analysis of pre-test and post-test scores showed that the participants experienced an increase in scores from an average score of 60.5 (SD = 12.1) to 80.5 (SD = 15.7). The paired t-test analysis yielded a p-value of <0.001, which indicates a significant difference between the pre-test and post-test scores. The training on making Samilakor herbal drink increased people's knowledge and understanding of COVID-19 and the immunomodulatory capabilities of herbal drinks. In addition, this training can be carried out online to cover a broader scope.